Body mass index and chronic unexplained gastrointestinal symptoms: an adult endoscopic population based study - Aro, P; Ronkainen, J; Talley, N J; Storskrubb, T; Bolling-Sternevald, E; Agréus, L (Gut, 2005)
Background: We aimed to determine whether obese subjects experience more gastro-oesophageal reflux (GORS) symptoms than normal subjects, and further to determine if this association was explained by oesophagitis or medications that lower oesophageal sphincter pressure. Methods: In a representative Swedish population, a random sample (n = 1001, mean age 53.5 years, 51% women) had upper endoscopy. GORS was defined as any bothersome heartburn or acid regurgitation. Results: The prevalence of obesity (body mass index ⩾30) was 16%; oesophagitis was significantly more prevalent in obesity (26.5%) than in normal subjects (9.3%). There were associations between obesity and GORS (odds ratio (OR) 2.05 (95% confidence interval (CI) 1.39, 3.01)), epigastric pain (OR 1.63 (95% CI 1.05, 2.55)), irritable bowel symptoms (OR 1.58 (95% CI 1.05, 2.38)), any abdominal pain (OR 1.59 (95% CI 1.08, 2.35)), vomiting (OR 3.11 (95% CI 1.18, 8.20)), retching (OR 1.74 (95% CI 1.1.3, 2.67)), diarrhoea (OR 2.2 (95% CI 1.38, 3.46)), any stool urgency (OR 1.60 (95% CI 1.04, 2.47)), nocturnal urgency (OR 2.57 (95% CI 1.33, 4.98)), and incomplete rectal evacuation (OR 1.64 (95% CI 1.09, 2.47)), adjusting for age, sex, and education. When subjects with oesophagitis and peptic ulcer were excluded, only diarrhoea, incomplete evacuation, and vomiting were significantly associated with obesity. The association between GORS and obesity remained significant adjusting for medication use (OR 1.9 (95% CI 1.3, 3.0)). Conclusions: GORS is associated with obesity; this appears to be explained by increased upper endoscopy findings in obesity.